The Role of Digital Literacy and Generic Skills on Student Physics Learning Outcomes - Darmaji Darmaji*; Astalini Astalini; Dwi Agus Kurniawan; Eko Nursulistiyo; Rahmat Perdana; Nirmala Prameswari (Universitas Syiah Kuala, 2023)
Digital literacy is a form of literacy that is very important for students to master along with technological developments. This digital literacy can be applied in learning, one of which is in learning physics. The urgency in this study is that it is hoped that the application of digital literacy in physics learning can improve student learning outcomes and generic skills. The purpose of this study was to determine the effect of applying digital literacy in learning physics on the learning outcomes and generic skills of class A and class B students. This study used a mixed methods research type. Then the data in this study were processed using SPSS 26 software to find values from the regression analysis. The results of the regression test function to determine the effect of implementing digital literacy on student physics learning outcomes. Based on the regression test, it is known that sig. 0.05, namely 0.001, which means that there is an effect of applying digital literacy in learning physics on student learning outcomes and 0.05, namely 0.000, which means that there is an effect of digital literacy on generic skills. The conclusion obtained is that there is an effect of applying digital literacy in physics learning to student learning outcomes and generic skills, where in class B the effect is greater in terms of grades or student learning outcomes